KARAKTERISASI MORFOLOGI TANAMAN KAKAO (Theobroma cacao L.) DAN HAMA YANG DITEMUKAN DI PT. PERKEBUNAN NUSANTARA XII BANYUWANGI - Alfin Fauziah Safitri; Ni Luh Watiniasih; Ni Made Suartini (Program Studi Biologi Universitas Udayana, 2024)
Cocoa (Theobroma cacao L.) is a commodity that has an important role in economic growth in Indonesia. Cacao cultivation business often experiences various obstacles, such as pest and disease attacks and the use of planting materials that have not been certified. The aims of this study were to determine the variations in the morphological characters of the cocoa plants and to identify the pests found and the kinship relationships among the cocoa plants. Research conducted at PT. Perkebunan Nusantara XII Kebun Kendenglembu Banyuwangi, East Java. Collecting data by conducting interviews, observation, document-tation, and literature study. Characterization was carried out on the leaves, flowers, fruits and stems of the cocoa plant, as well as observing the symptoms of damage caused by pests to the cocoa plant. The six cocoa clones had different morphological characteristics in fruit length, fruit circumference, thickness of the sclerotic layer, thickness of the inner groove of the fruit, thickness of the outer groove of the fruit, leaf length, leaf width, petiole length, and stem circumference. The six cocoa clones can be grouped into two groups where the clones in one group are thought to have a close kinship relationship because they are in the same lineage and based on the similarity of the morphological characters of the fruit. The pests found were fruit-sucking ladybugs, caterpillars, mealybugs, squirrels and slugs.